Pattern Visual Evoked Potentials in the Assessment of Visual Acuity in Malingering - Gundogan, Fatih C.; Sobaci, Gungor; Bayer, Atilla (Ophthalmology (Rochester, Minn.), 2007)
To determine the value of pattern visual evoked potential (PVEP) testing with 5 consecutive check-size patterns in presumably malingering draftees. Case–control study. The study group included 111 military conscripts (124 eyes) whose visual abnormalities could not be explained by the findings of ophthalmologic, neurological, and psychiatric examinations. The control group was comprised of 111 age- and gender-matched healthy subjects without ocular problems, except with refraction. The latency and amplitude of P 100 for 5 consecutive patterns (2°, 1°, 30′, 15′, and 7′) corresponding to visual acuities (VAs) of 0.1, 0.2, 0.4, 0.7, and 1.0, respectively, were measured in both groups. Pattern VEP–estimated VA (PVEP-VA) was determined by the VA corresponding to the smallest check size, with normal interocular variance in unilateral cases and normative data for P 100 latency and amplitude values in bilateral cases. The best-performed VA was determined with a battery of clinical tests for malingering (VA obtained after simulation examination techniques [VA aset]). Comparison of PVEP-VA to VA aset. In pure malingerers, PVEP-VA was 1.0 (normal recordings in all patterns) for all eyes (20 eyes), and all subjects were proven to be malingerers (true positives). Of the exaggerators, 81 (77.8%) with an underlying ophthalmic disorder had a ±1–Snellen line discrepancy between PVEP-VA and VA aset. Pattern VEP–estimated VA was well correlated with VA aset ( r = 0.670). Sensitivity, specificity, and positive and negative predictive values of PVEP in functional visual loss were found to be 97.2%, 62.5%, 94.5%, and 76.9%, respectively. Pattern VEP testing with 5 consecutive check-size patterns may define VA objectively, especially in pure malingers; however, PVEP results should be evaluated in the context of the clinical examination, which remains the gold standard method to reveal the malingering.